Innovation in Language Learning and Teaching The Case of the Middle East and North Africa - Reinders, Hayo.; Coombe, Christine; Littlejohn, Andrew; Tafazoli, Dara.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This edited collection presents a study of innovation in teaching, learning, assessment and teacher development practices in the Middle East and North Africa (MENA). The thirteen research-based chapters in this collection examine recent innovations in English language teaching, drawing on classroom, administrative and learning experiences from seven of the countries in the region. The major trends analyzed across the volume include the language skills of reading and writing and the prevalence of technology and technology-enhanced instruction. It highlights that innovative teaching, learning and assessment practices that are now in place in virtually all levels of English language teaching and learning from primary school to university to adult education sectors, and reflects on possible ways forward for innovation in the field of ELT. This book will provide valuable insight for scholars of applied linguistics and practitioners working in language policy, .
Chapter 1. Innovation in Language Learning and Teaching: The Case of the MENA; Christine Coombe, Hayo Reinders, Andrew Littlejohn & Dara Tafazoli -- Chapter 2. Refugees from MENA learning languages: Progress, Principles and Proposals; John Traxler, Elena Barcena & Timothy Read -- Chapter 3. Plugging the gap: Supporting primary school teachers to create culturally appropriate ELT materials; Sarah Rich, Sam Weekes, Maryam al Jardani & Salima al Sinani -- Chapter 4. Task-based learning and teaching: The case in Egypt; Deena Boraie, Ebtihal El Badry & Maged Habashy -- Chapter 5. Innovation in writing instruction: Towards nurturing confident, motivated, and academically honest L2 writers; Fatima Esseili -- Chapter 6. Innovation in reading in the United Arab Emirates; Melanie Gobert & Helene Demirci -- Chapter 7. Reading for science: Anatomy as a metaphor for a holistic college-wide innovation; Roger Nunn, Caroline Brandt, Asli Hassan & Curtis Bradley -- Chapter 8. Towards English for Academic Purposes curriculum reform: Linguistic, educational or political considerations?; Elana Spector-Cohen, Lisa Amdur, Ingrid Barth, Rosalie Sitman & Linda Weinberg -- Chapter 9. The evolution of research paper course; Andrew Littlejohn & Sandhya R. Mehta; Chapter 10. Developing communication skills through participation in course-based undergraduate research experiences; Robert Craig & Brian Bielenberg -- Chapter 11. Preparing for a digital future: CALL teacher education in Iran; S. Susan Marandi -- Chapter 12. Online language teacher education for a challenging innovation: Towards critical language pedagogy for Iran; Arman Abednia & Graham Crookes -- Chapter 13. Telecollaboration among Qatari and U.S. undergraduates in a multicultural course: Opportunities and obstacles; Zohreh R. Eslami, Valerie Hill-Jackson, Svetlana Kortes & Lobat Asadi.
Keywords: Language and languages -- Study and teaching; Intercultural communication; Educational technology; Language policy; Language Education; Intercultural Communication; Language Teaching and Learning; Digital Education and Educational Technology; Language Policy and Planning